Mrs. Fletcher [large type] : a novel - Perrotta, Tom, 1961- (Thorndike Press, a part of Gale, a Cengage Company, 2017)
Eve Fletcher is dealing with empty-nest syndrome when she gets a text message from an anonymous number, "U R my MILF!" Over the months that follow, Eve develops an interest in a porn website called MILFateria.com, which features the erotic exploits of ordinary, middle-aged women like herself. As her online fixations begin to spill over into real life, romantic possibilities threaten to upend her quiet suburban existence. Miles away at the state college, her son Brendan is floundering in a college environment that challenges his white-dude privilege and shames him for his outmoded, chauvinistic ideas of sex.